MENINGKATKAN HASIL BELAJAR MATERI GELOMBANG MENGGUNAKAN SIMULASI CROCODILE PHYSICS PADA MODEL THINK- PAIR-SHARE - Gumrowi, Ahmad (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This action research aims at increasing students' achievement on the topic Gelombang for the second year studens of MAN 1 Pesisir Barat by using Crocodile Physic Simulation of Think-Pair-Share model. The students' achievement on the wave topic is the research's object, whereas the subject of the research is the students of MAN 1 Pesisir Barat.This action research is conducted within three cycles. Each cycle consists of plan, action, observation and reflection. Based on the result of analysis it is found that Crocodile Physics Simulation of Think-Pair-Share model is able to increase the students' achievement of the wave topic.The average students achievement increases from 58,77 becomes 65,70 or 11,80% increasingly during Cycle I, increases from 65,70 to 71,37 or 8,63% during Cycle II, and increases up to 74,30 or 4,11% in Cycle III. By comparing between Pre Research and Cycle III there is 26,43% increases. Besides, the completeness of learning increases from 26,67 during Pre Research to 46,67 during Cycle I, increases 63,33 during Cycle II and becomes 86,67 in Cycle III. By comparing the 58,77 during Pre ResearÃ§h there is an increasing students achievement up to 60%.